2019
DOI: 10.2147/jpr.s210366
|View full text |Cite
|
Sign up to set email alerts
|

<p>Open cubital and carpal tunnel release using wide-awake technique: reduction of postoperative pain</p>

Abstract: PurposeThis study aimed to compare the efficacy of and patient satisfaction with the wide-awake local anesthesia with no tourniquet (WALANT) technique in open cubital and carpal tunnel release surgery.MethodsFrom January 2016 to February 2017, 20 cubital tunnel syndrome (CuTS) patients were in a wide-awake (WA) group and 22 in a general (GA) anesthesia group in . Also, 20 carpal tunnel syndrome (CTS) patients were in a WA group, 22 in a local anesthesia (LA) group, and 20 in a GA group. Injection pain, periope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 16 publications
0
20
1
3
Order By: Relevance
“…For minor hand surgeries, Ki Lee et al 53 reported a significantly longer duration of anesthetic effect, lower injection pain, and lower postoperative pain scores until the first day after surgery for WALANT patients versus those who received conventional anesthesia. Huang et al 54 found that WALANT patients with distal radius fractures experienced less postoperative pain than general anesthesia patients, whereas Kang et al 55 found that using WALANT for cubital and carpal tunnel surgery was superior for pain. These findings suggest effective analgesia can be achieved safely without the additional side effects of traditional anesthetic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…For minor hand surgeries, Ki Lee et al 53 reported a significantly longer duration of anesthetic effect, lower injection pain, and lower postoperative pain scores until the first day after surgery for WALANT patients versus those who received conventional anesthesia. Huang et al 54 found that WALANT patients with distal radius fractures experienced less postoperative pain than general anesthesia patients, whereas Kang et al 55 found that using WALANT for cubital and carpal tunnel surgery was superior for pain. These findings suggest effective analgesia can be achieved safely without the additional side effects of traditional anesthetic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that moving common hand procedures from the main operating room (OR) to a minor procedure room provides benefits in waste reduction, cost-efficiency, time savings, and risk attenuation without compromising patient safety and satisfaction. 1 -10 In the setting of a small procedure room or clinic, the full OR sterile procedure can be consolidated to “minor field sterility.” This practice involves fewer disposable items, which results in a reduction of excess OR waste and costs. 11 Additionally, these procedure rooms require less preparation than the main OR, resulting in decreased turnover and wait times.…”
Section: Introductionmentioning
confidence: 99%
“…Chapman et al similarly saw no difference in post-operative consumption of opioids between WALANT and general anesthesia patients, concluding that age and gender were more predictive of opioid consumption than anesthesia type [61]. Kang et al did, however, observe that there was less need for supplemental opioid injections in the wide-awake group than in the general anesthesia group (12% versus 35%, respectively), showing that there is a strong possibility that WALANT could be beneficial in reducing the need for opioids [62]. Additionally, Dar et al demonstrated that WALANT patients who were not prescribed opioids following surgery experienced lower pain scores at 14 days post-operation than patients who underwent similar procedures under MAC [63].…”
Section: Opioid Usementioning
confidence: 95%